Ecdysone Receptor (EcR) and Ultraspiracle Protein (USP) Genes From Conopomorpha sinensis Bradley Eggs: Identification and Expression in Response to Insecticides - Yao, Qiong; Xu, Shu; Dong, Yizhi; Quan, Linfa; Chen, Bingxu (Frontiers in Physiology, 2020)
Conopomorpha sinensis Bradley (Lepidoptera: Gracilariidae) is the dominant insect pest of litchi (chinensis Sonn.) and longan (Euphoria longan Lour.) fruit trees. Management of this pest species is a challenging task due to its cryptic borer behavior. Controlling C. sinensis at the egg stage is the best alternative strategy to chemical control of C. sinensis adults. However, thorough studies regarding the indirect and sublethal effects of chemicals on the different developmental stages of C. sinensis are insufficient. In this study, the effect of some insecticides was evaluated on C. sinensis eggs. The ovicidal activity of chlorbenzuron, abamectin, chlorantraniliprole, and λ-cyhalothrin was confirmed by morphological observation of the defects in C. sinensis eggs. Moreover, we characterized four essential ecdysone receptor proteins in insects (i.e., two isoform ecdysone receptors [EcR: CsEcRA. CsEcRB] and two isoform ultraspiracle proteins [USP: CsUSP1, CsUSP2]) from C. sinensis eggs. The CsEcRA, CsEcRB, CsUSP1, and CsUSP2 genes consisted of 1521-, 1614-, 1410-, and 1236-bp open reading frames which encoded proteins of 506, 527, 469, and 413 amino acid residues, respectively. Furthermore, the embryonic differential responses of CsEcRs, CsUSPs, and vitellogenin receptor (VgR: CsVgR) to insecticides were evaluated by qRT-PCR. Among the five tested genes, CsVgR and CsUSP1 were the most sensitive to all the tested insecticides, with fold change of the expression diminished by 4.27–8.70 times compared with untreated control insects. The data suggests that these insecticidal compounds regulate the expression of these specific proteins, which might eventually lead to reduced viability of C. sinensis eggs. We present here the first data providing molecular elucidation of ecdysone receptor genes and their differential responses to insecticides in C. sinensis eggs. Together with our previous report of insecticide sublethal effects on two reproduction-related genes in C. sinensis adults, CsVgR and CsUSP1 seem to be appropriate molecular parameters for the evaluation of insecticide impact on C. sinensis. This study exemplifies the potential utility of transcriptional measurement of nuclear receptors as the molecular biomarkers for ecotoxicological evaluations of ovicidal impact of insecticides.